2015
DOI: 10.4314/mmj.v27i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Breast enlargement in Malawian males on the standard first line antiretroviral therapy regimen: Case reports and review of the literature

Abstract: 1. A 35-year-old man was referred to Zomba Central Hospital in June 2014 from a health center with a presenting complaint of enlarged breasts. This had started gradually, approximately six months prior. He did not experience any pain or discharge from his nipples. He had no other complaints and felt generally healthy. In early 2013 he had been concomitantly diagnosed with pulmonary tuberculosis and HIV infection and was started on cotrimoxazole prophylaxis and antiretroviral therapy (ART) with tenofovir, lamiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
5
8
0
Order By: Relevance
“…This finding is similar to other case series where efavirenz was discontinued [12, 13, 15], but it is noteworthy that other studies have reported improvement in patients, despite continuation of efavirenz [4, 8, 9]. Time to complete resolution was slow in our case series and was comparable to other studies that have reported a resolution time ranging from two to nine months [4, 6, 8, 12, 15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is similar to other case series where efavirenz was discontinued [12, 13, 15], but it is noteworthy that other studies have reported improvement in patients, despite continuation of efavirenz [4, 8, 9]. Time to complete resolution was slow in our case series and was comparable to other studies that have reported a resolution time ranging from two to nine months [4, 6, 8, 12, 15].…”
Section: Discussionsupporting
confidence: 91%
“…A small case series from Nigeria reported on six patients with efavirenz-associated gynaecomastia, all of which resolved after withdrawal of efavirenz [12]. Two cases of efavirenz-associated gynaecomastia were reported from Malawi, both of which improved after switching efavirenz to nevirapine [13]. …”
Section: Discussionmentioning
confidence: 99%
“…4 This case report builds upon these prior findings with the description of two additional cases of gynaecomastia from Mozambique. The two males infected with HIV were on stable ART containing EFV.…”
Section: Respiratorymentioning
confidence: 58%
“…6 In several other studies associations between gynaecomazia and specific antiretroviral drugs, including stavudine and efavirenz, have been reported. 5 In most cases, gynaecomastia cases reported occurred after prolonged efavirenz exposure. Efavirenz is known to be associated with gynaecomazia, as when switched from efavirenz, gynaecomazia improved/resolved in the majority.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological gynaecomazia is self-limiting and occurs in newborns, adolescents, and the elderly. 5 The prevalence of asymptomatic gynaecomazia is 60 to 90% in neonates, 50 to 60% in adolescents, and up to 70% in men aged 50 to 69 years. 3 It has to be distinguished from pseudogynecomastia and lipomastia, which are both forms of fat accumulation in the breasts.…”
Section: Discussionmentioning
confidence: 99%